Sztuczne raje prawdopodobieństwa. O funkcjach negowania w wierszu pt. Dworzec Wisławy Szymborskiej i jego angielskim przekładzie autorstwa Stanisława Barańczaka i Clare Cavanagh - Anna Stanisz (Postscriptum Polonistyczne)
The aim of this article is to interpret Szymborska’s poem entitled The Railroad Station and its English translation, from the point of view of the key poetics of negation. From the point of view of linguistics, literary studies, and translation studies, the poem is demonstrative of the variety of forms of negation and their semantic functions used in Szymborska’s entire oeuvre. The translators use numerous and various forms of formal and semantic negation as well, but they lack the central pragmatic negation. Szymborska doubts whether ‘our’ world is the best of possible worlds: since there is only one course of events, ‘the paradise of probability’ is ‘artificial’; the world is a burial ground of possibilities that did not come true.